Gastrostomy Tube Use after Transoral Robotic Surgery for Oropharyngeal Cancer. (8th July 2013) - Al-khudari, Samer; Bendix, Scott; Lindholm, Jamie; Simmerman, Erin; Hall, Francis; Ghanem, Tamer
Abstract : Objective . To evaluate factors that influence gastrostomy tube (g-tube) use after transoral robotic surgery (TORS) for oropharyngeal (OP) cancer. Study Design/Methods . Retrospective review of TORS patients with OP cancer. G-tube presence was recorded before and after surgery at followup. Kaplan-Meier and Cox hazards model evaluated effects of early (T1 and T2) and advanced (T3, T4) disease, adjuvant therapy, and free flap reconstruction on g-tube use. Results . Sixteen patients had tonsillar cancer and 13 tongue base cancer. Of 22 patients who underwent TORS as primary therapy, 17 had T1 T2 stage and five T3 T4 stage. Seven underwent salvage therapy (four T1 T2 and three T3 T4). Nine underwent robotic-assisted inset free flap reconstruction. Seventeen received adjuvant therapy. Four groups were compared: primary early disease (PED) T1 and T2 tumors, primary early disease with adjunctive therapy (PEDAT), primary advanced disease (PAD) T3 and T4 tumors, and salvage therapy. Within the first year of treatment, 0% PED, 44% PEDAT, 40% PAD, and 57% salvage patients required a g-tube. Fourteen patients had a temporary nasoenteric tube (48.3%) postoperatively, and 10 required a g-tube (34.5%) within the first year. Four of 22 (18.2%) with TORS as primary treatment were g-tube dependent at one year and had received adjuvant therapy. Conclusion . PED can be managed without a g-tube after TORS. Similar feeding tube rates were found for PEDAT and PAD patients. Salvage patients have a high rate of g-tube need after TORS.